Phytochemical Investigation and Antimicrobial Activity of Agastache rugosa Growing in Xinjiang, China - Gong, H.Y.; Ding, J.B.; Zhu, M.; Liu, H.B.; Tian, S.G.; Ma, X.M. (Asian Journal of Chemistry, 2012)
It is reported that Agastache rugosa from Xinjiang of China has great biological/medicinal values. In this study, the phytochemistry and antimicrobial activity in different parts of A. rugosa growing in Xinjiang, China were investigated for the first time. Water, methanol, ethanol, chloroform and petroleum ether extracts of flower, stem, leaf from A. rugosa were prepared with successive extraction by the method of ultrasound. The detection of various phytochemicals of each extract was studied under standard methods. It was found that flower, stem, leaf parts have the same chemical constituents simultaneously, but have different chemical constituents. The essential oil of A. rugosa was extracted by the method of hydrodistillation. It showed strong inhibition against Staphylococcus aureus, Escherichia coli of essential oil from flower part; strong inhibition against Escherichia coli, Blastomyces albicans of essential oil from leaf part, and low activity against Blastomyces albicans from flower and leaf parts.